The Effect of Parameters in Cryogenic Treatment on Mechanical Properties of Tool Steel: A Review - Ekaputra, Ronaldus Caesariano; Mochtar, Myrna Ariati (Journal of Materials Exploration and Findings, 2023)
Tool steel is classified as special alloy steel which proposed as dies or mold materials as their high mechanical properties and dimensional stability. In order to improve tool steel’s mechanical properties, heat treatment process, especially, cryogenic treatment is conducted. Cryogenic treatment is done by exposing tool steel material at sub-zero liquid/gas media after heated at austenite temperature. This process significantly affects the martensite phase transformation increase and avoids retained austenite emersion. In particular, the higher martensite volume fraction, the higher hardness and wear resistance value of tool steel. It had been proven that adjusting critical process parameters of cryogenic treatment (temperature process, soaking period, and tempering process) shall increase the efficiency of improving mechanical properties of cryo-treated finished product.